Exploring the challenges to drone-aided inspections in construction site management - Khorombi, Shadrack (University of the Witwatersrand, Johannesburg, 2024)
The construction industry, marked by its complexity and evolving standards, demands attention and commitment to quality. To guarantee that works are going according to plan, standards and regulations, in terms of quality and compliance, routine inspection strategies are implemented as an intrinsic part of the project management plan. Construction inspections are generally performed as a contractual obligation to enable an independent view of construction works and their progress for key stakeholders and the client. However, traditional inspection techniques are generally laborious and risky. Inspectors are often exposed to exterior elements; unfavourable conditions; intrinsic risks. Despite all of this, inspectors are still unable to obtain in-depth information on some of the surfaces due the inability to access surfaces or structures to optimal proximity. Drone technology has been proposed as an alternative method to traditional inspection for safer and more efficient inspections. This study endeavoured to explore key challenges to the implementation of drone technology for construction inspections. The methodological approach that the researcher adopted to achieve the research aim encompassed a qualitative method with document analysis, case study and interviews selected as data collection strategies. Techniques to gather empirical information required included observations and semi-structured interview questions. To present findings that are valid, reliable and generalisable, NVivo software was used as a data analysis tool where content analysis and thematic analysis were employed as data analysis strategies. The utilisation of qualitative, inductive case studies within an interpretivist paradigm was considered necessary to contextualise and deepen the understanding of the nature and occurrence of the challenges impeding key role players from full adoption of drone technology for construction site inspection processes. Key findings entail the lack of capital and resource allocation, concerns about transparency and contractual accountability, and the need for clear evidence of return on investment. Technical complexity, disruption to site activities, lack of interest from key stakeholders, capacity issues, and connectivity issues were also uncovered as challenges in the adoption of drone-aided inspections. Additionally, the findings encompassed strategies to overcome challenges impeding the optimal use of drones in construction projects. This study evaluates the current state and potential for drone technology adoption within the South African construction industry, highlighting practical challenges encountered during actual deployments. By proposing solutions such as streamlining regulatory processes and enhancing stakeholder collaboration, the research offers valuable pathways to optimise drone technology implementation during construction documentation and management.
A Dissertation submitted in fulfilment of the requirements of Master of Science in Building by Research, to the Faculty of Engineering and Built Environment, School of Construction Economics and Management. University of the Witwatersrand, Johannesburg, 2024
Keywords: Drone technology; Construction; Inspections; UCTD; SDG-9: Industry, innovation and infrastructure; SDG-4: Quality education